Quality assurance systems of pharmaceutical distributors in low-income and middle-income countries: weaknesses and ways forward - Nebot Giralt, A; Bourasseau, A; White, G; Pouget, C; Tabernero, P; Van Assche, K; Ravinetto, R (BMJ Publishing Group, 2020)
Introduction Access to quality-assured medicines is an essential prerequisite for universal health coverage, and pharmaceutical distributors play an important role to assure the quality of medicines along the supply chain. Methods We retrospectively assessed the compliance with WHO quality standards, that is, the Model Quality Assurance System for Procurement Agencies (MQAS) or the good distribution practices (GDP), of a convenience sample of 75 public, private-for-profit and non-for-profit distributors, audited by QUAMED in 14 low-income and middle-income countries (LMICs) between 2017 and 2019. We calculated the compliance per quality assurance activity, and we defined the percentage of compliant distributors, that is, the percentage (%) of distributors with MQAS or GDP levels of >2 for each activity. Results The distributors in our sample were mainly private for-profit (66/75). Only one MQAS-audited distributor out of 11 was found compliant with all MQAS-activities, while none out of 64 GDP-assessed distributors were found compliant with all GDP activities. The GDP-assessed distributors were generally less compliant with WHO standards than MQAS-audited distributors. Common weaknesses and strengths were observed. The activities with lowest compliance were quality control, and physical storage conditions, while those with highest compliance were warehouse organisation and stock control. Conclusions The quality systems of pharmaceutical distributors in LMICs remain weak. For preventing harm caused by poor-quality medicines, a comprehensive and stringent regulatory oversight should be urgently implemented; the WHO MQAS-standards and GDP-standards should be incorporated in national regulations; and reliable information on the quality systems of distributors (and manufacturers from which they buy) should be publicly available.